Genetic tests in children with steroid-resistant nephrotic syndrome - Hae Il Cheong (The Korean Society of Nephrology, 2020)
Steroid-resistant nephrotic syndrome (SRNS) is a common cause of chronic kidney disease in children, and a considerable number of patients progress to end-stage renal disease. SRNS is a highly heterogeneous disorder, both clinically and genetically, and more than 50 monogenic causes of SRNS, including isolated and syndromic forms, have been identified. Recent large-cohort studies indicate that at least 30% of childhood-onset SRNS cases are genetic. The benefits of definitive molecular diagnosis by genetic testing include the avoidance of unnecessary and potentially harmful diagnostic procedures (e.g., kidney biopsy) and treatment (e.g., steroid and immunosuppressants), detection of rare and potentially treatable mutations (e.g., coenzyme Q10 biosynthesis pathway defect), prediction of prognosis (e.g., posttransplant recurrence), and providing precise genetic counseling. Furthermore, the identification of novel disease-causing genes could provide new insights into the pathogenic mechanisms of SRNS. Therefore, whenever accessible and affordable, genetic testing is recommended for all pediatric patients with SRNS, and should certainly be performed in patients with a higher probability of genetic predisposition based on genotype-phenotype correlation data. The genetic testing approach should be determined for each patient, and clinicians should, therefore, be aware of the advantages and disadvantages of methods currently available, which include Sanger sequencing, gene panel testing, and whole-exome or whole-genome sequencing. Importantly, the need for precise and thorough phenotyping by clinicians, even in the era of genomics, cannot be overemphasized. This review provides an update on recent advances in genetic studies, a suggested approach for the genetic testing of pediatric patients with SRNS.